2017
DOI: 10.1167/iovs.16-20742
|View full text |Cite
|
Sign up to set email alerts
|

Is Choroidal or Scleral Thickness Related to Myopic Macular Degeneration?

Abstract: Citation: Wong CW, Phua V, Lee SY, Wong TY, Cheung CMG. Is choroidal or scleral thickness related to myopic macular degeneration? Invest Ophthalmol Vis Sci. 2017;58:907-913. DOI:10.1167/iovs.16-20742 PURPOSE. The relative contribution of mechanical and vascular factors to the pathogenesis of myopic macular degeneration (MMD) is unclear. To address this gap, we examined the association of choroidal thickness (CT) and scleral thickness (ST) with MMD.METHODS. Prospective, clinic-based case series of 62 eyes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 31 publications
7
68
4
Order By: Relevance
“…The correlation with the severity of maculopathy was found to be stronger for choroidal thickness than it was for scleral thickness, suggesting that a vascular mechanism related to choroidal ischaemia may be playing a more prominent role in the pathogenesis of the condition than a mechanical mechanism involving scleral stretch. Studies have also shown that the reductions in visual acuity observed in myopic maculopathy, are significantly correlated with macular choroidal thickness, further supporting a role for the choroid in these conditions …”
Section: Choroidal Changes In Myopiamentioning
confidence: 85%
See 1 more Smart Citation
“…The correlation with the severity of maculopathy was found to be stronger for choroidal thickness than it was for scleral thickness, suggesting that a vascular mechanism related to choroidal ischaemia may be playing a more prominent role in the pathogenesis of the condition than a mechanical mechanism involving scleral stretch. Studies have also shown that the reductions in visual acuity observed in myopic maculopathy, are significantly correlated with macular choroidal thickness, further supporting a role for the choroid in these conditions …”
Section: Choroidal Changes In Myopiamentioning
confidence: 85%
“…In a study using swept‐source OCT, examining posterior scleral and choroidal thickness of eyes with myopic macular degeneration, a thinner choroid was found to be strongly positively correlated with the severity of myopic macular degeneration . The correlation with the severity of maculopathy was found to be stronger for choroidal thickness than it was for scleral thickness, suggesting that a vascular mechanism related to choroidal ischaemia may be playing a more prominent role in the pathogenesis of the condition than a mechanical mechanism involving scleral stretch.…”
Section: Choroidal Changes In Myopiamentioning
confidence: 99%
“…Significant thinning of the choroid in myopia and its relationship with visual function have been widely studied. 23,31,32 The choroid provides most of the oxygen demand of the photoreceptors. 11,12,33 Thinning of the choroid might result in a lack of oxygen, which is indispensable for photoreceptor metabolism and photosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies had reported a negative correlation between mChT and MM severity. 23,31 The thinning of choroidal thickness may contribute to various myopic pathologic changes, such as chorioretinal atrophy, LCs, and CNV. 20,[32][33][34][35] However, the definition of MM in these studies was based on atrophic and neovascular changes, and there are no studies reporting a correlation between choroidal thinning and myopic tractional changes.…”
Section: This Study Is To the Best Of Our Knowledge The Firstmentioning
confidence: 99%